Nonocarbolines A-E, β-Carboline Antibiotics Produced by the Rare Actinobacterium Nonomuraea sp. from Indonesia - Gian Primahana; Chandra Risdian; Tjandrawati Mozef; Enge Sudarman; Matthias Köck; Joachim Wink; Marc Stadler (MDPI AG, 2020)
During the course of our ongoing screening for novel biologically active secondary metabolites, the rare Actinobacterium, Nonomuraea sp. 1808210CR was found to produce five unprecedented β-carboline derivatives, nonocarbolines A−E (1−5). Their structures were elucidated from high-resolution mass spectrometry, 1D and 2D nuclear magnetic resonance spectroscopy, and the absolute configuration of 4 was determined by using the modified Mosher method. Nonocarboline B (2) displayed moderate antifungal activity against Mucor hiemalis, while nonocarboline D (4) exhibited significant cytotoxic activity against the human lung carcinoma cell line A-549 with the IC50 value of 1.7 µM.